FORMULASI DAN UJI AKTIVITAS GEL ANTI ACNE BERBASIS EKSTRAK DAUN RAMANIA (Bouea macrophylla Griffith) TERHADAP BAKTERI Cutibacterium acnes - Muhammad Fadhil Kamil; Fitriyanti Fitriyanti; Wahyudin Bin Jamaludin (FACULTY OF PHARMACY, INSTITUT ILMU KESEHATAN BHAKTI WIYATA, 2026)
Background: Acne is an inflammatory condition of the pilosebaceous unit involving infection by Cutibacterium acnes. Ramania leaves (Bouea macrophylla) contain flavonoids, saponins, and tannins with known antibacterial properties. Objective: This study aimed to formulate a methanolic extract gel of Ramania leaves and evaluate its physical and organoleptic qualities as well as its antibacterial activity against C. acnes. Method: The extract was obtained via maceration and formulated in a carbopol-based gel with concentrations of 5%, 7.5%, 10%, 15%, and 20%. Physical evaluations included organoleptic testing, homogeneity, pH, viscosity, adhesiveness, and spreadability. Antibacterial activity was tested using the well diffusion method. Results: showed all gel formulas met standard physical and organoleptic criteria. The 5% extract gel demonstrated the largest inhibition zone against C. acnes (22.8 mm ± 2.06). Concentrations above 10% showed decreased effectiveness, likely due to saturation or physical instability. Conclusion: The 5% Ramania leaf extract gel is the most effective and stable formulation for topical anti-acne application